Goldenhar Syndrome with Dextrocardia and Right Pulmonary Hypoplasia: An Unusual Association - Nagendra Chaudhary; Sandeep Shrestha; Hemant Kumar Halwai (Case Reports in Genetics)
Goldenhar syndrome (GS), a rare condition, occurring due to defect in development of first and second branchial arches, is characterized by a combination of various anomalies involving face, eyes, ears, vertebrae, heart, and lungs. The etiology of GS is not fully known, although various hypotheses have been proposed along with its genetic association and many other causes. Facial asymmetry and hypoplasia of the mandible are characteristic features of GS along with microtia and preauricular appendages and pits. Dextrocardia or pulmonary hypoplasia in GS has previously been reported separately. We report a 7-year-old female child of GS with combination of anomalies, dextrocardia, and pulmonary hypoplasia, which is a rare association.